Proceedings of the 2nd ACM SIGOPS/EuroSys European Conference on Computer Systems 2007 2007
DOI: 10.1145/1272996.1273023
|View full text |Cite
|
Sign up to set email alerts
|

Fine grained kernel logging with KLogger

Abstract: Understanding the detailed behavior of an operating system is crucial for making informed design decisions. But such an understanding is very hard to achieve, due to the increasing complexity of such systems and the fact that they are implemented and maintained by large and diverse groups of developers. Tools like KLogger -presented in this paper -can help by enabling fine-grained logging of system events and the sharing of a logging infrastructure between multiple developers and researchers, facilitating a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…The harder part was measuring the duration of the handler. For this purpose we have instrumented the kernel by using klogger, a kernel logger we developed that supports efficient fine-grain events [20]. While the code is integrated into the kernel, its activation at runtime is controlled by applying a special sysctl call using the /proc file system.…”
Section: Direct Overheadmentioning
confidence: 99%
“…The harder part was measuring the duration of the handler. For this purpose we have instrumented the kernel by using klogger, a kernel logger we developed that supports efficient fine-grain events [20]. While the code is integrated into the kernel, its activation at runtime is controlled by applying a special sysctl call using the /proc file system.…”
Section: Direct Overheadmentioning
confidence: 99%
“…This total time is accumulated in numerous short bursts of CPU activity, interspersed by system activity (handling interrupts or system calls) and possibly the execution of other processes. Obtaining data about the length of CPU bursts requires precise instrumentation, using tools such as KLogger [219]. Using such tools, it is found that typical bursts are very short, and in particular they are much shorter than the operating system's time quantum (Figure 9.6) -so much so as to make the operating system quantum irrelevant.…”
Section: Process Runtimesmentioning
confidence: 99%
“…The actual source code of the Linux kernel is modified to include LTT macros in specified functions and LTT based data structures for holding the trace information. Other tools that fall into this category are K42 [14] and KLogger [18]. All of these only provide tracing.…”
Section: Related Workmentioning
confidence: 99%